THE EFFECT OF HIGHER EDUCATION EXPANSION ON THE MARRIAGE MARKET IN CHINA - Tian, Maomao; Campos, Maria Rebecca A (PEOPLE: International Journal of Social Sciences, 2020)
China’s higher education expansion policy started in 1999. It brought about rapid increase not only in the number of college and postgraduate enrollment, but also changed its gender ratio. A shift to female dominance under the traditional marriage mode further increased the risk of matching difficulties and failures. This paper assessed the impact of college enrollment expansion in the marriage market, evaluated the consequences of rapid expansion of higher education through the perspective of the marriage market, specifically, for females. Use Census data between 2005 and 2015 to analyze the marriage choice of graduate students, and urban survey were used to analyze the marriage choices of undergraduates. SPSS 22.0 was used, testing results show that significantly negative association of college enrollment expansion with the marriage market. The greater the density of interventions for enrollment, the higher the decline in marriage rates. However, women who have higher education have chosen to be single. The recommendations are strengthen marriage awareness in college; determine intervention measures, adjust the university curriculum and educate college students about marriage and childbearing; help graduates prepare for participation in the marriage market in order to produce a family; and enrich relevant knowledge and information that will lead them to accurate expectations to avoid search failure in the marriage market.